PEMETAAN KONDISI PUSTAKAWAN SWASTA SEBAGAI BASIS PENYUSUNAN KEBIJAKAN PEMBINAAN PUSTAKAWAN SWASTA - Khosyi Maulana; Farli Elnumeri (Jurnal IPI (Ikatan Pustakawan Indonesia), 2018)
This study discusses the needs analysis of guidance to librarians who are in institutions or non-governmental institutions. The guidance includes the recruitment pattern, the main task (work system), professional development, career path and performance appraisal and payroll. The formulation of the problem in this research is how the model of guidance to librarians in non-governmental institutions. This research uses mixed method. Research with mixed methods is a pragmatic paradigmatic research. Librarian conditions in non-governmental institutions, employment levels and career librarians are not clear and have not been established yet. This case have been found in every librarian of non-governmental institutions. 48.4% of librarians in non-governmental institutions have not had the opportunity to attend education and training, 26.3% have not earned decent salary and earned a raise. Based on this matter, the guidance of librarians in non-governmental institutions should be set forth in a regulation that contains at least about career patterns, educational and training opportunities and provincial minimum wage. The laws that are going to set have to consider the condition of librarian in non-govermental institution.